The given equation of the circle is:
![4x^2+4y^2-24x+16y=48](https://img.qammunity.org/2023/formulas/mathematics/college/msgk3jb9lchp3nc0dvycw8isuiic9xo20l.png)
We can start by simplifying this equation by dividing both sides by 4:
![\begin{gathered} (4x^2)/(4)+(4y^2)/(4)-(24x)/(4)+(16y)/(4)=(48)/(4) \\ x^2+y^2-6x+4y=12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qdtxeib8cfua6bm42bwwgfcb0cy7p8b8qy.png)
Now, if we subtract 12 from both sides it is written in general form:
![\begin{gathered} x^2+y^2-6x+4y-12=0 \\ \text{ General form:} \\ x^2+y^2+ax+by+c=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u5wn94rj2278flg6kr15qbpgkmh8ucvoum.png)
Where a, b and c correspond to:
![\begin{gathered} a=-2x_0 \\ b=-2y_0 \\ c=x_0^2+y_0^2-r^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5mv1jivmsg6gta6l3qkok2qzsc25hm835t.png)
The coordinates of the center of the circle are (x0,y0) and r is the radius.
By replacing the known values we can obtain the center and radius as follows:
![\begin{gathered} -6=-2x_0 \\ x_0=(-6)/(-2) \\ x_0=3 \\ \\ 4=-2y_0 \\ y_0=(4)/(-2) \\ y_0=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/buy5zdok90o2rcasyg5ofomu21vo97k90d.png)
The center of the circle is located at (3,-2).
Let's find the radius:
![\begin{gathered} -12=3^2+(-2)^2-r^2 \\ -12=9+4-r^2 \\ -12=13-r^2 \\ -12-13=-r^2 \\ -25=-r^2 \\ r^2=25 \\ r=√(25) \\ r=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qcabn37ykdd5z9on3c2s519vbi2xwcz83h.png)
The radius of the circle is 5.
PART B.
By knowing the coordinates of the center and the radius, the graph of the circle looks like this:
PART C.
To find the intercepts, we need to make x=0 and solve for y, and then make y=0 and solve for x as follows:
![\begin{gathered} 0^2+y^2-6*0+4*y-12=0 \\ y^2+4y-12=0 \\ Apply\text{ the quadratic equation:} \\ y=(-4\pm√(4^2-4(1)(-12)))/(2(1)) \\ y=(-4\pm√(64))/(2) \\ y=(-4\pm8)/(2) \\ y=(-4-8)/(2)=(-12)/(2)=-6\text{ and }y=(-4+8)/(2)=(4)/(2)=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/13qhkuz3r56j14k592q6xyzijb96ayk3sw.png)
The y-intercepts are y=-6 and y=2.
Now let's find the x-intercepts:
![\begin{gathered} x^2+0^2-6x+4*0-12=0 \\ x^2-6x-12=0 \\ \text{ Apply the quadratic equation:} \\ x=(-(-6)\pm√((-6)^2-4(1)(-12)))/(2(1)) \\ x=(6\pm√(84))/(2) \\ x=(6\pm9.2)/(2) \\ x=(6-9.2)/(2)=(-3.2)/(2)=-1.6\text{ and }x=(6+9.2)/(2)=(15.2)/(2)=7.6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6f4mcohqiqsj0gyq1jmz2uhke5l2bvhqef.png)
The x-intercepts are x=-1.6 and x=7.6